Islam Nusantara: Relasi Islam dan Budaya Lokal - Khabibi Muhammad Luthfi (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
The objective of this article is to explore the concept of Islam Nusantara (IN) observed from the structural theory of Islam and local culture relation, along with the reason why IN is developed into the concept of the Islamic proselytizing Rahmatan lilalamin by the intellectual Nahdhatul Ulama (NU). It comes from the NU Intellectuals claim that IN is the mediator in the controversy of Islam and local culture relation, moreover in the global scale it is going to be proselytized in the International, whereas the IN is still regarded as an issue and has not fulfilled the knowledge standard yet. Through philosophical approach, socio-anthropolinguistics based on the data in www.nu.or.id and topic analysis as its data analysis, it is found that the intellectual of NU used eight approaches to concept the IN. The IN set that Islam influences Indonesian culture and the INs success and ability to dialogue with Indonesian culture trigger the intellectual NU to promote it to the International.